2020
DOI: 10.1136/thoraxjnl-2019-214000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mast cells: a novel mechanism by which nintedanib may elicit anti-fibrotic effects

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease which presents a grave prognosis for diagnosed patients. Nintedanib (a triple tyrosine kinase inhibitor) and pirfenidone (unclear mechanism of action) are the only approved therapies for IPF, but have limited efficacy. The pathogenic mechanisms of this disease are not fully elucidated; however, a role for mast cells (MCs) has been postulated.ObjectivesThe aim of this work was to investigate a role for MCs in IPF and to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 50 publications
(67 reference statements)
6
23
2
4
Order By: Relevance
“…TIMP1 was specifically observed in mast cells within the fibrotic areas. These findings correlate to a recent study by Overed-Sayer et al [ 20 ] that showed induction of mast cells in IPF and could explain the lack of positive staining in the HLFs. Moreover, this group showed that nintedanib inhibits mast cell survival and activation and thus provides a novel additional mechanism by which this drug may exert anti-fibrotic effects in patients with IPF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…TIMP1 was specifically observed in mast cells within the fibrotic areas. These findings correlate to a recent study by Overed-Sayer et al [ 20 ] that showed induction of mast cells in IPF and could explain the lack of positive staining in the HLFs. Moreover, this group showed that nintedanib inhibits mast cell survival and activation and thus provides a novel additional mechanism by which this drug may exert anti-fibrotic effects in patients with IPF.…”
Section: Discussionsupporting
confidence: 92%
“…exposure to the IPF-CM at the mRNA and the protein levels (p < 0.05, Figure 1D,E tionally, protein levels of plasminogen activator inhibitor-1 (PAI-1, encoded PINE1) were elevated (Figure 1E). 20) showed that IPF tissues expressed significantly higher HIF1A, TIMP1, SERPINE1 and VEGFA mRNA levels (p < 0.05, Figure 2A). IHC staining of paraffin tissue samples from patients with IPF and normal tissue samples revealed that HIF1α is abundant in the IPF tissue.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In NSCLC the number of tryptase positive MCs linearly correlates with microvascular density, confirming the important role of this enzyme in regulating tumor angiogenesis (Ibaraki et al, 2005;Carlini et al, 2010). Inhibition of c-kit and its ligand SCF could hamper mast cell infiltration into the TME, preventing degranulation and thereby producing a synergizing anti-angiogenic effect (Huang et al, 2008;Overed-Sayer et al, 2020).…”
Section: The Role Of Tumor Angiogenesis In Nsclcmentioning
confidence: 77%
“…However, nintedanib alone only reduced the mobilization of MDSCs into peripheral blood (208). Overed-Sayer et al, 2020, found that the number of lung mast cells is increased in IPF and was found to be negatively correlated with baseline lung function in humans (209). Additionally, they found that nintedanib, but not pirfenidone, inhibited human fibroblast mediated mast cell survival through stem cell factor receptors and reduced the recruitment of mast cells into the lungs of BPF in rats (209).…”
Section: Nintedanibmentioning
confidence: 99%